Elimination of macrostep-induced current flow nonuniformity in vertical GaN PN diode using carbon-free drift layer grown by hydride vapor phase epitaxy. (16th March 2018) - Fujikura, Hajime; Hayashi, Kentaro; Horikiri, Fumimasa; Narita, Yoshinobu; Konno, Taichiro; Yoshida, Takehiro; Ohta, Hiroshi; Mishima, Tomoyoshi
Abstract: In vertical GaN PN diodes (PNDs) grown entirely by metal–organic chemical vapor deposition (MOCVD), large current nonuniformity was observed. This nonuniformity was induced by macrosteps on the GaN surface through modulation of carbon incorporation into the n-GaN crystal. It was eliminated in a hybrid PND consisting of a carbon-free n-GaN layer grown by hydride vapor phase epitaxy (HVPE) and an MOCVD-regrown p-GaN layer. The hybrid PND showed a fairly low on-resistance (2 mΩ cm 2 ) and high breakdown voltage (2 kV) even without a field plate electrode. These results clearly indicated the strong advantages of the HVPE-grown drift layer for improving power device performance, uniformity, and yield.